The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/978-3-319-05269-4_20
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inference of Cancer Pathways and Tumor Progression from Cross-Sectional Mutation Data

Abstract: Recent cancer sequencing studies provide a wealth of somatic mutation data from a large number of patients. One of the most intriguing and challenging questions arising from this data is to determine whether the temporal order of somatic mutations in a cancer follows any common progression. Since we usually obtain only one sample from a patient, such inferences are commonly made from cross-sectional data from different patients. This analysis is complicated by the extensive variation in the somatic mutations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…Vandin et al [20] introduced Pathway Linear Progression Model (PLPM) which was defined for an integer > 1 as an integer linear program problem of looking for * = ∈ ( ) ( , ), and showed that the problem is an NP-hard problem. To solve it more efficiently, we construct a weighted gene network based on exclusive degree between each pair of genes to simplify the relationships between the genes and to significantly reduce the computational complexity.…”
Section: Constructing a Gene Network Based On Approximate Exclusivitymentioning
confidence: 99%
See 4 more Smart Citations
“…Vandin et al [20] introduced Pathway Linear Progression Model (PLPM) which was defined for an integer > 1 as an integer linear program problem of looking for * = ∈ ( ) ( , ), and showed that the problem is an NP-hard problem. To solve it more efficiently, we construct a weighted gene network based on exclusive degree between each pair of genes to simplify the relationships between the genes and to significantly reduce the computational complexity.…”
Section: Constructing a Gene Network Based On Approximate Exclusivitymentioning
confidence: 99%
“…Second, how to detect driver pathways, which are frequently perturbed with a large number of tumor cells, and give rise to the product of tumorigenic properties, such as cell angiogenesis, proliferation or metastasis [1], [2], [3], [12], [13], [14], [15], [16], [17]. Third, how to determine temporal orders of the driver mutations in cancer patients [18], [19], [20], [21], [22]. The first question can usually be solved by comparing mutation frequencies across different individuals [6], [7], [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations